Analisis Tingkat Kepuasan Pengunjung Taman Wisata Graha Mangrove Kota Bontang - Irna tahir, Irna tahir; Oktawati, Nurul Ovia; susilo, heru (Jurnal Pembangunan Perikanan dan Agribisnis, 2025)
ABSTRACTSuccess in managing a fishing business needs a careful attention to the services provided. This study aims to determine the level of visitors' satisfaction at Graha Mangrove tourism park. This study utilizes accidental sampling method. The analysis of the data utilizes the analysis method of Community Satisfaction Index (CSI) and Importance Performance Analysis (IPA). According to the results of the analysis, the Community Satisfaction Index (CSI) is at 62.76, which means that it is within the category of good service quality. In addition, Importance Performance Analysis (IPA) shows that the satisfaction indicators that should be considered and become the main priority for improvements at Graha Mangrove tourism park are indicators that are in the quadrant A.